What has electron microscopy contributed to Alzheimer's research?. (December 2015) - Baloyannis, Stavros J
Electron microscopy has enlarged the visual horizons of the morphological alterations in Alzheimer's disease (AD). Study of the mitochondria and Golgi apparatus in early cases of AD revealed the principal role that these important organelles play in the drama of pathogenic dialog of AD, substantially affecting energy production and supply, and protein trafficking in neurons and glia. In addition, study of the morphological alterations of the dendritic arbor, dendritic spines and neuronal synapses, which are associated with mitochondrial damage, may reasonably interpret the clinical phenomena of the irreversible decline of the mental faculties and an individual's personality changes. Electron microscopy also reveals the involvement of microvascular alterations in the etiopathogenic background of AD.